Unveiling the Post-Pandemic Pedagogical Shift: A Bibliometric Odyssey into Educational Technology Research on the Scopus Database (2020-2023) - Amien, Moch Yusril Rahmatillah; Maksum, Muh. Nur Rochim; Anshori, Ari; Mubarok, Fahmi Ulum Al (Universitas Muhammadiyah Surakarta, 2023)
The aim of this research is to map and analyze the development of research on educational technology in publications indexed in Scopus. The method used is bibliometric analysis, which focuses on the study of publications on the topic of